On Reuben G. Jones synthesis of 2-hydroxypyrazines - Pierre Legrand; Yves L. Janin (Beilstein Journal of Organic Chemistry, 2022)
In 1949, Reuben G. Jones disclosed an original synthesis of 2-hydroxypyrazines involving a double condensation between 1,2-dicarbonyls and α-aminoamides upon treatment with sodium hydroxide at low temperature. This discovery turned out to be of importance as even today there are no simple alternatives to this preparation. Across the years, it was employed to prepare 2-hydroxypyrazines but some of its limits, notably regioselectivity issues when starting from α-ketoaldehydes, certainly hampered a full-fledged generation of pyrazine-containing new chemical entities of potential interest in medicinal chemistry. The present text describes some insights and improvements, such as the unprecedented use of tetraalkylammonium hydroxide, in the reaction parameters affecting the regioselectivity and yield when starting from phenylglyoxal and two α-aminoamides. We also suggest a mechanism explaining the counterintuitive occurrence of 3,5-substituted-2-hydroxypyrazine as the major reaction product.